What's the question though?
Answer:
= -√6
Step-by-step explanation:
1) collect like terms by subtracting coefficients:
3√6 - 4√6
(3-4)√6
2) calculate (3-4):
(3-4)√6
-1√6
3) the coefficient of -1 does not have to be written, but the negative sign remains:
-1√6
-√6
so therefore:
-√6 is your answer
Answer: r = 11
Step-by-step explanation:
We know that the point (-2, r) lies on the graph of:
2*x + y = 7.
Then, if we that point is on the graph of the equation, we can replace the values and we will have:
2*(-2) + r = 7
and now we solve this for r-
-4 + r = 7
r = 7 + 4 = 11
r = 11